FINISH FIRST : WINNING CHANGES EVERYTHING - Hamilton, Scott, 1958-; Fallon, Allison (Nashville, Tennessee : W PUBLISHING GROUP, AN IMPRINT OF THOMAS NELSON, 2018)
Go for the win! Achieve excellence and be better than you've ever been!
Bibliography: pages 179-181.
Keywords: Success; Self-realization